2014
DOI: 10.1177/1054773814533124
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Managing Patients’ Pain May Experience Moral Distress

Abstract: Bedside nurses care for patients with pain every day but the task is often challenging. A previous qualitative study that investigated nurses' experiences as they treated patients with pain suggested that nurses may suffer from moral distress if they are unsuccessful in providing adequate pain relief. As 20 of the original 48 nurses interviewed described frustration and distress when constrained from doing the right thing to provide pain relief for their patients, the purpose of this secondary qualitative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Other studies have shown moral distress in nurses related to pain management, including challenges in nurse/physician communication, the perception that the provider has written ineffective orders, and lack of pain education. 4,5,15 Nurses also interact more frequently with patients and family members, who may request to under- or overtreat symptoms or treat the signs of imminent death that may not be causing a patient discomfort. Relieving suffering at the end of life, providing patient- and family-centered care, and concerns about hastening death can be perceived to be in conflict and contribute to moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown moral distress in nurses related to pain management, including challenges in nurse/physician communication, the perception that the provider has written ineffective orders, and lack of pain education. 4,5,15 Nurses also interact more frequently with patients and family members, who may request to under- or overtreat symptoms or treat the signs of imminent death that may not be causing a patient discomfort. Relieving suffering at the end of life, providing patient- and family-centered care, and concerns about hastening death can be perceived to be in conflict and contribute to moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Often, structural barriers such as a lack of resources and time and ineffective policy lead to nurses’ moral distress (LeBaron et al., 2014; Varcoe, Pauly, Storch, Newton, & Kara Makaroff, 2012). In a phenomenological study, Bernhofer and Sorrell (2014) found nurses caring for patients for whom they are unable to provide appropriate pain relief suffered moral distress. Nurses who knew how to provide proper pain management but were hindered from doing so experienced the most distress.…”
Section: Overview Of Maid In Canadamentioning
confidence: 99%
“…Inadequate education of physicians and other clinicians regarding pain management is not unusual 33 . This knowledge deficit contributes to biases against patients with chronic pain, makes clinicians hesitant to treat these patients, reduces the effectiveness of their pain management, and creates moral distress in nurses charged with their care 33,38 . The Centers for Disease Control and Prevention plans to partner with other organizations to provide clinicians with education on pain management options and methods to minimize risks during opioid therapy 12 …”
Section: The Need For Improvement In Postsurgical Pain Managementmentioning
confidence: 99%
“…Nurses, surgeons, and anesthesiologists may be accustomed to established “communication silos” and autonomy at their institution 59‐61 . Nurse‐physician hierarchies and the feeling among nurses that their clinical opinion is not valued may contribute to their hesitation to advocate for their patients and to their frustration and moral distress at not being able to alleviate patients’ pain 38 …”
Section: The Need For Improvement In Postsurgical Pain Managementmentioning
confidence: 99%